The effect of alloyed nickel on the short-term high temperature oxidation behaviour of Co–Re–Cr-based alloys. (April 2015) - Wang, L.; Gorr, B.; Christ, H.-J.; Mukherji, D.; Rösler, J.
Highlights: The alloying of 15 at.% Ni improves the oxidation resistance of Co–17Re–23Cr significantly. The improvement relies on promoting the formation of protective Cr2 O3 layer. Calculation of thermodynamics and diffusion kinetics were conducted. Results show Ni does not promote Cr2 O3 nucleation but enhances the Cr diffusion in matrix. Slow growing Co(Ni)O layer facilitates the selective oxidation of Cr. Abstract: The effect of Ni on the oxidation behaviour of the alloy Co–17Re–23Cr (at.%) is studied. The results show that the alloying of 15 at.% Ni improves the alloy oxidation resistance significantly by promoting the formation of a protective Cr2 O3 layer. This effect can be attributed at least partially to the enhancement of Cr diffusion by Ni in the metallic Co–Re–Cr–Ni matrix. Moreover, the formation of relatively slow growing Co(Ni)O solid–solution in the transient stage supports the lateral growth of Cr2 O3 nuclei and thus accelerates the establishment of the compact chromia layer.